Konseling Kelompok dengan Pendekatan Rational Emotive Behavior Therapy dalam Meningkatkan Motivasi Belajar Siswa Keluarga Broken Home - Tria Utami; Sri Ilham Nasution (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2026)
Learning motivation is an important factor in students' academic success, especially for students from broken homes who often experience decreased motivation due to family conflict, lack of attention, and emotional instability. This study aims to examine the group counseling process using the Rational Emotive Behavior Therapy (REBT) approach in improving the learning motivation of students from broken homes at SMK Negeri 1 Martapura. This study used a descriptive qualitative method involving 10 students as research subjects. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that group counseling with the REBT approach resulted in positive changes in students' cognitive, behavioral, and emotional aspects. Cognitively, students were able to change irrational thought patterns to more rational ones and accept family conditions more healthily. Behaviorally, there was an increase in attendance, participation in learning, and responsibility for assignments. Emotionally, students became more confident, more open, and showed a decrease in withdrawal behavior. These findings indicate that REBT group counseling provides meaningful support in improving students' learning motivation in the school context.